Effectiveness and Efficiency of Medical Check-Up Service Quality With The Use of Terra (Survey Study at Harapan Keluarga Hospital, Mataram City) - Siar, Cindy Advenia; Mulyani, Sri Rochani; Sofia, Etty (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Periodic health checks represent a key behavioral pattern among both health service users and health providers within a healthcare facility. The present study aims to analyze the effectiveness and efficiency of Medical Check Up (MCU) service quality using the TERRA framework—Tangibles, Empathy, Reliability, Responsiveness, and Assurance—at Harapan Keluarga Mataram Hospital, one of the leading private hospitals in Mataram City. This research employed a descriptive qualitative design, in which data were collected through direct observation, in-depth interviews, documentation reviews, and the study of relevant literature. Informants included hospital directors, physicians, nurses, patients, and subject-matter experts selected to provide comprehensive insights into the MCU service process. Data analysis was conducted using NVivo12 software through Matrix Coding and Project Map Node visualization to identify dominant factors influencing service performance. The findings indicate that reliability, empathy, and assurance constitute the most influential dimensions in determining the effectiveness and efficiency of MCU service quality. These factors strongly shape patient trust, perceived professionalism, and overall satisfaction. Conversely, the dimensions of tangibles and responsiveness were found to have an influence, but their contribution was relatively less significant compared to the other three dimensions. Based on these results, efforts to improve MCU service quality should prioritize sustaining high levels of reliability, empathy, and assurance, as these components form the core determinants of service excellence. Strengthening all five dimensions collectively is essential because the TERRA framework functions as an integrated set of complementary elements that jointly support optimal healthcare service delivery.